Shares Valuation with Fundamental Analysis in Investment Decisions (Study of Companies Listed on the Indonesian Stock Exchange for the 2022 Period) - Paujiah, Andini Nur; Muhamad, Fadilah; Salsabila , Raihani; Marlita, Rini; Suherman, Ujang (PT FORMOSA CENDEKIA GLOBAL, 2024)
Shares are a very popular investment product today. Moreover, shares can achieve very high returns compared to other investment products. However, shares are also closely related to investment risk. Therefore, to avoid the risks of investing in shares, you should develop various strategies before buying shares. The method used in this paper is quantitative descriptive. Determining the sample in this study used a Purposive Sampling technique with the criteria of food and beverage companies that were consistently listed on the IDX and distributed dividends to their shareholders in 2022, thus obtaining 5 sample companies, namely MLBI, AALI, ULTJ, INDF, MYOR. The data collection technique is by using documentation analysis. And the data analysis technique uses manual calculations using the stock assessment formula TATO, ROE, EPS, CR, DER, DPR, and the PER and PBV share price assessment formulas. Based on fundamental analysis and stock price assessment, these 5 food and beverage companies are worthy of investment. But the INDF company is the most worthy company to invest in. Even though the ROE is relatively low (10%), the INDF company's PER is below 15x (6.04) indicating that the share price is still considered cheap by investors.